Direct Detection of Local Electric Polarization in the Interfacial Region in Ferroelectric Polymer Nanocomposites. Issue 21 (29th March 2019) - Peng, Simin; Yang, Xiao; Yang, Yang; Wang, Shaojie; Zhou, Yao; Hu, Jun; Li, Qi; He, Jinliang
Abstract: Ferroelectric polymer nanocomposites are widely used in capacitive energy storage, electrocaloric refrigeration, and mechanical energy harvesting due to their exceptional electric polarization property and ease of fabrication. It is generally considered that the abnormal performance of ferroelectric nanocomposites stems from the interfacial region between the polymer matrix and embedded nanoparticles. However, direct evidence of the distinct local electric polarization property at the interfacial region is not yet accessible. Herein, a modified Kelvin probe force microscopy (KPFM) method with nanoscale spatial resolution is reported for direct detection of local polarization property at the matrix/particle interface in ferroelectric nanocomposites. Typical ferroelectric nanocomposites are studied using the present method. It is quantitatively probed that the electric polarization at matrix/particle interfacial region is higher than the polymer matrix under applied electric fields. Taking into account the enhanced local electric polarization gauged by the modified KPFM, the dielectric property of ferroelectric polymer nanocomposites matches with bulk experimental characterizations, indicating that the established method is reliable. It is anticipated that the present method, opening up new possibilities in understanding the matrix/particle interfacial region, may help with judicious design and engineering of high‐performance ferroelectric polymer nanocomposites. Abstract : A modified Kelvin probe force microscopy method is developed for direct detection of local electric polarization with nanoscale spatial resolution. It is quantitatively probed that in ferroelectric polymer nanocomposites the electric polarization at the matrix/particle interface is higher than the polymer matrix, which explains the exceptional performance of bulk materials.